Curcumolide reduces diabetic retinal vascular leukostasis and leakage partly via inhibition of the p38MAPK/NF-κ B signaling. Issue 8 (15th April 2017) - Cai, Yuan; Li, Wencan; Tu, Hongfeng; Chen, Nanmei; Zhong, Zhipeng; Yan, Pengcheng; Dong, Jianyong
Graphical abstract: Abstract: Retinal inflammation in a hyperglycemic condition is believed to play a crucial role in the development of diabetic retinopathy, and targeting inflammatory mediators is a promising strategy for the control of diabetic retinopathy. Curcumolide, a novel sesquiterpenoid with a unique 5/6/5 tricyclic skeleton, was isolated from Curcuma wenyujin. In this study, we demonstrate that treatment with curcumolide alleviated retinal inflammatory activities both in vitro and in vivo in a STZ-induced diabetic rat model and in TNF-α-stimulated HUVECs. Curcumolide alleviated retinal vascular permeability and leukostasis and attenuated the overexpression of TNF-α and ICAM-1 in diabetic retinas. Moreover, curcumolide also inhibited inducible p38 MAPK and NF-κB activation and the subsequent induction of proinflammatory mediators. These data suggest potential treatment strategies against diabetic retinopathy, particularly in the early stages of the disease.